Wear-resistant bucket tooth laser cladding-composite casting integrated forming process for super-large excavator bucket and wear-resistant bucket tooth

By using an integrated laser cladding-composite casting process, combined with gradient preheating, dovetail groove mechanical interlocking, and rare earth flux, the problems of hard layer peeling and insufficient interface bonding strength in bucket teeth under extreme working conditions have been solved, resulting in composite bucket teeth with ultra-high wear resistance and long service life.

CN120924963APending Publication Date: 2025-11-11HAINAN ZHIHE LITUO TECHNOLOGY PARTNERSHIP (LLP)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510834211.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing bucket tooth manufacturing technology faces problems such as easy peeling of hard layer, insufficient interfacial bonding strength and crack propagation caused by thermal stress accumulation under extreme working conditions. Although existing patents have optimized wear resistance and interfacial bonding, they are still limited by the sensitivity of process parameters, limited material compatibility and high energy consumption costs.

Method used

A laser cladding-composite casting integrated forming process is adopted. Through gradient preheating, dovetail groove mechanical interlocking and rare earth flux synergistic effect, a molybdenum boride/vanadium carbide/titanium nitride composite coating is constructed on a low alloy steel substrate. This achieves a metallurgical-mechanical dual combination between the cladding layer and the cast steel substrate. The residual stress distribution is optimized through directional cooling and tempering heat treatment.

Benefits of technology

It significantly improves the bonding reliability between the wear-resistant layer and the substrate, suppresses the accumulation of residual stress at the interface, achieves ultra-high wear resistance and impact resistance, and meets the long service life requirements of extreme working conditions such as mining and hard rock crushing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120924963A_ABST
    Figure CN120924963A_ABST
Patent Text Reader

Abstract

According to the laser cladding-composite casting integrated forming process for the wear-resistant bucket tooth for the super-large excavator bucket and the wear-resistant bucket tooth, laser cladding and casting technologies are adopted for collaborative manufacturing, and laser power is adopted for cladding iron-based alloy powder containing molybdenum boride / vanadium carbide / titanium nitride composite ceramic particles layer by layer, so that a surface micro-texture wear-resistant layer is formed. A dovetail groove array is innovatively designed on the back face of the base plate, a gradient preheating process is matched, an aluminum oxide hollow ball thermal buffer medium is added in a resin sand casting mold, and interface metallurgical bonding is achieved through molten steel pouring. And the interface oxygen content is smaller than or equal to 0.01 wt% by adopting rare earth scaling powder, quenching-tempering heat treatment is combined, and finally the wear-resistant bucket tooth with the tooth top surface hardness being 1400-1800 HV, the matrix hardness being 300-400 HV and the interface bonding strength being larger than or equal to 500 MPa is prepared. The technology effectively solves the technical problems that a traditional bucket tooth is insufficient in wear resistance and an interface is easy to strip through cladding layer superhard ceramic phase strengthening and casting matrix toughness optimization, and is suitable for manufacturing wear-resistant parts of large engineering machinery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to composite materials for wear-resistant parts, and more particularly to an integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets, which involves laser cladding and composite casting, and the wear-resistant bucket teeth themselves. Background Technology

[0002] The current manufacturing of bucket teeth in the construction machinery industry faces a dilemma regarding the compatibility of core materials and processes. While integral casting offers advantages in large-scale production, its limitations stem from the metallic properties of the base material. A hardness index of HV≤400 results in a wear rate of 0.3-0.5 mm / h for the wear-resistant layer under high-stress conditions such as mining and construction crushing, leading to a typical service life of less than 800 hours for a single set of bucket teeth. Surface welding technology, through hard alloy coatings, can increase the hardness of the working surface to 800-1000 HV, but this process has inherent flaws: the welding process, with a heat input of 15-20 kJ / cm, creates an 8-12 mm wide heat-affected zone, causing coarsening of the base material grains and reducing the impact toughness of the bucket tooth body by 40%-60%. Simultaneously, the brittle transition layer formed between the coating and the base material exhibits micro-peeling after 500 cycles of impact at a bond strength of 300 MPa, with the hard layer peeling rate exceeding 35% in actual working conditions.

[0003] Composite casting, as a third-generation solution, constructs a gradient material system through the embedding of cemented carbide preforms. Theoretically, this can achieve a metallurgical bond between a wear-resistant layer with a hardness of 1200-1500 HV and a tough matrix with a hardness of 300-350 HV. However, the interface problem between dissimilar materials has become a technical bottleneck: the difference in thermal expansion coefficients between cemented carbide and cast steel results in a shrinkage mismatch of 0.25-0.35% at a casting temperature of 1600℃, leading to the formation of an oxide inclusion band 0.1-0.3 mm wide at the interface. Related studies show that the oxygen content in this region exceeds the standard value by 3-5 times, forming a discontinuous bonding interface, resulting in an actual bonding strength of less than 250 MPa. Residual stress testing shows that there is a tensile stress of 600-800 MPa at the interface, and under a contact stress of 3.5 GPa, the crack propagation rate reaches 0.8 × 10⁻⁶. -4 mm / cycle, significantly shortening the fatigue life of bucket teeth.

[0004] Patent CN108160923A discloses a method for preparing particle-reinforced iron-based ultra-wear-resistant bucket teeth. Its core technology involves in-situ generation of a TiC+VC dual-phase reinforcing layer on the bucket tooth surface via self-propagating high-temperature synthesis (SHS), achieving a balance between high hardness and matrix toughness. Advantages include: synergistic reinforcement by TiC and VC dual-phase particles, uniform particle distribution, and tight interfacial bonding, significantly improving wear resistance; adaptability to different working conditions such as sand, coal mines, and rocks by adjusting coating parameters; and the combination of vacuum lost foam casting and heat treatment processes, resulting in a matrix (high-manganese steel or medium-low alloy steel) with both ductility and impact resistance. The integration of SHS with the casting process simplifies the process and is suitable for large-scale production. However, this technology still has limitations: the hardness of the reinforcing layer is limited by the intensity of the self-propagating reaction, making it difficult to cope with extreme wear environments; process control is complex, and the yield rate is prone to fluctuations; the matrix material adaptability is insufficient; and the high-temperature casting (1480-1570℃) and large amount of precious metal powders (Ni, Mo) lead to high energy consumption and costs.

[0005] Patent CN114774912A discloses a method for preparing a self-lubricating ceramic high-temperature wear-resistant coating by laser cladding in situ. The core technology involves forming a composite coating of TiC / TiN / Cr3C2 ceramic phase and graphite / hexagonal boron nitride (h-BN) on the surface of an H13 steel mold using laser cladding, achieving a synergistic enhancement of high wear resistance and self-lubricating function. The main advantages of this technology are: the coating's microhardness reaches 1200-1450 HV; the laser cladding process enables a metallurgical bond between the coating and the substrate, resulting in high interfacial bonding strength and avoiding the problem of easy peeling of traditional coatings; the process has high integration, is suitable for repairing or modifying complex mold surfaces, and is easily automated in production. However, this technology still has certain limitations: the process parameters are highly sensitive, requiring strict matching of laser power, scanning speed, and ball milling conditions; even slight deviations can easily lead to porosity or cracks in the coating; the high proportion of titanium powder and h-BN in the raw materials, coupled with the high energy consumption of the laser equipment, significantly increases production costs; the coating thickness range and interfacial stress distribution are not clearly defined, and thick coatings may be at risk of cracking due to the accumulation of thermal stress; the technology verification is only for H13 steel, and its compatibility with other mold materials has not been explored.

[0006] Traditional bucket tooth manufacturing technologies, while achieving the integration of wear-resistant layers and tough substrates through integral casting, surface welding, and composite casting, face core challenges under extreme conditions, including easy peeling of the hard layer, insufficient interfacial bonding strength, and crack propagation caused by thermal stress accumulation. Existing patents have optimized wear resistance and interfacial bonding through in-situ synthesis of dual-phase particles using SHS and laser cladding of self-lubricating ceramic coatings, but these are still limited by process parameter sensitivity, limited material compatibility, and high energy consumption costs. This invention aims to overcome these technical bottlenecks by employing an integrated laser cladding-composite casting process. Through gradient preheating, dovetail groove mechanical interlocking design, and the synergistic effect of rare earth flux, a molybdenum boride / vanadium carbide / titanium nitride composite coating is constructed on a low-alloy steel substrate, achieving a metallurgical-mechanical dual bond between the cladding layer and the cast steel substrate. Furthermore, directional cooling and tempering heat treatment optimize residual stress distribution, ultimately producing composite bucket teeth with ultra-high wear resistance, impact toughness, and long service life, meeting the demands of extreme working conditions such as mining and hard rock crushing. Summary of the Invention

[0007] To overcome the shortcomings of the existing technology, this invention provides an integrated laser cladding-composite casting process for wear-resistant bucket teeth of ultra-large excavator buckets, as well as wear-resistant bucket teeth. By combining laser cladding and casting in a coordinated manufacturing process, and integrating gradient preheating, dovetail groove mechanical interlocking, and rare earth flux interface purification technology, the metallurgical bonding and thermal stress distribution between the cladding layer and the cast steel substrate are optimized, effectively solving the problems of insufficient wear resistance and interface peeling of traditional bucket teeth.

[0008] The objective of this invention can be achieved through the following technical solutions:

[0009] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0010] S1: Substrate pretreatment and laser cladding: Low alloy steel substrate is selected, and after surface sandblasting and rust removal, it is preheated. Then, using laser cladding equipment, molybdenum boride reinforced iron-based alloy powder is clad layer by layer on the pre-embedded metal substrate to form a wear-resistant preform.

[0011] S2: Composite sand mold preparation and pre-embedding: Place the clad wear-resistant preform into the resin sand mold, and preheat the preform and sand box before casting;

[0012] S3: Alloy melting and casting: Melt cast steel, control the temperature of molten steel, quickly pour into the mold, use the high temperature of molten steel to partially remelt the back of the substrate, and apply flux to the back of the substrate before casting.

[0013] S4: Directional cooling and sand removal: After the casting has cooled naturally, the mold is opened, the residual sand particles are removed by vibration, the gating and riser are cut off and the flash is ground off.

[0014] S5: Tempering and heat treatment strengthening: Quenching and tempering treatment of castings.

[0015] Furthermore, this includes the following steps:

[0016] S1: Substrate pretreatment and laser cladding: Low alloy steel substrate is selected. After surface sandblasting and rust removal, it is preheated to 200-300℃. Using laser cladding equipment, molybdenum boride reinforced iron-based alloy powder is clad layer by layer on the pre-embedded metal substrate. The laser power is 3.5-6.0kW, the spot diameter is 1.5-3.0mm, and the scanning speed is 6-12mm / s, forming a wear-resistant preform with surface microtexture.

[0017] S2: Composite sand mold preparation and pre-embedding: The cladding preform is placed as an embedded block into the resin sand mold. Before casting, the preform and the sand box are preheated using a gradient preheating process.

[0018] S3: Alloy melting and casting: Melt cast steel, control the melting temperature to 1600-1650℃, and quickly cast at a casting temperature of 1520-1560℃. Use the high temperature of the molten steel to partially remelt the back of the substrate. Apply flux to the back of the substrate before casting.

[0019] S4: Directional cooling and sand removal: After the casting has cooled naturally to below 600℃, the mold is opened, the residual sand particles are removed by vibration, the gating and riser are cut off and the flash is ground off.

[0020] S5: Tempering and heat treatment strengthening: After holding at 850-900℃, oil cooling / water quenching, followed by tempering at 500-600℃ for 2.0-4.0 hours and air cooling.

[0021] Furthermore: the back of the pre-embedded metal substrate is an array of dovetail grooves with a depth of 0.3-1.2mm, a groove spacing of 2-5mm, a groove width of 0.5-1.5mm, and a surface roughness Ra≤50μm.

[0022] Furthermore, the gradient preheating process includes preheating the cladding layer to 300-450℃ and preheating the resin sand casting mold to 200-300℃, with the heating method being a combination of induction heating and infrared radiation heating.

[0023] Furthermore: the gradient preheating adopts a staged temperature control strategy. The cladding layer is first heated to 300℃ at a rate of 10-15℃ / s, held for 5-15 minutes, and then heated to the target temperature. The casting sand mold adopts infrared radiation zone heating.

[0024] Furthermore, the alloy composition of the molybdenum boride-reinforced iron-based alloy powder is 8-20 wt% Mo2B, 5.0-15 wt% vanadium carbide, 3.0-8.0 wt% titanium nitride composite ceramic particles and iron powder, wherein the vanadium carbide particle size is 10-50 μm and the titanium nitride particle size is 20-80 μm.

[0025] Furthermore, 2-10% alumina hollow spheres are locally added to the resin sand casting mold as a heat buffer medium. The alumina hollow spheres are uniformly mixed with the molding sand and oriented in the area where the wear-resistant preform is placed. Their low thermal conductivity slows down the solidification rate of the interface area and matches the thermal expansion difference between the cladding layer and the substrate.

[0026] Furthermore: the flux contains 1-5% rare earth oxides, namely Y2O3 or CeO2, and the rare earth elements release active rare earth elements during the decomposition process.

[0027] Furthermore, a dovetail groove array is reserved between the wear-resistant preform and the resin sand mold to accommodate the infiltration of casting metal to form a metallurgical bonding transition layer.

[0028] Furthermore: the tip region of the bucket teeth is covered by a laser cladding layer with a hardness of HV1400-1800; the substrate is low-carbon alloy steel with a hardness of HV300-400 and an interface bonding strength ≥500MPa.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. By using the dovetail groove array structure design and the infiltration of cast metal to form a mechanical interlocking effect, combined with the interface purification effect of rare earth flux, metallurgical bonding is achieved, breaking through the bottleneck of the interface bonding strength of dissimilar materials, and significantly improving the bonding reliability between the wear-resistant layer and the substrate.

[0031] 2. By adopting a gradient preheating process and directional arrangement of alumina hollow sphere thermal buffer medium, the thermal expansion difference between the cladding layer and the cast steel substrate is precisely matched, effectively suppressing the accumulation of residual stress at the interface and avoiding crack initiation and propagation problems.

[0032] 3. The innovative design integrates superhard ceramic phase reinforcement and toughness matrix optimization, and forms a composite structure with a hardness gradient transition through laser cladding and casting processes, achieving ultra-high wear resistance under extreme working conditions while maintaining impact resistance. Attached Figure Description

[0033] Figure 1 A process flow diagram of the preparation method of the present invention is shown;

[0034] Figure 2 A photograph of the tissue structure of the cladding transition region in Example 1 is shown;

[0035] Figure 3 A photograph of the matrix tissue morphology of Example 1 is shown. Detailed Implementation

[0036] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. It should be noted that those skilled in the art can make various changes and modifications without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0037] Example 1

[0038] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets, and the wear-resistant bucket teeth themselves, the molding process including the following steps:

[0039] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 50μm. The substrate is then preheated to 250℃ in an induction heating furnace and held for 15 minutes. A laser with a power of 4.2kW, a spot diameter of 2.0mm, and a cladding scanning speed of 8mm / s is used to clad molybdenum boride-reinforced iron-based alloy powder layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 8wt% Mo2B, 12wt% vanadium carbide (20μm particle size), 6wt% titanium nitride composite ceramic (60μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a micro-textured surface.

[0040] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 0.8 mm, a groove width of 1.0 mm, a groove spacing of 3 mm, and a surface roughness Ra = 50 μm. Subsequently, a furan resin sand mold containing 5% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.5 mm gap. Before casting, the preform is gradually heated to 300°C at a rate of 12°C / s using induction heating and held for 5 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 250°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0041] S3: The cast steel is melted at 1620℃ and rapidly cast at a pouring temperature of 1540℃. Before casting, a flux containing 1.0% rare earth oxides is applied to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxides are Y₂O₃ or CeO₂, which release active rare earth elements during decomposition.

[0042] S4: After the casting has cooled naturally to 550℃, it is opened from the mold. The residual sand particles are cleaned by a vibrating sand removal machine. Then the gating gate is cut off and the flash is ground until the surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0043] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 880℃ for 1.5 hours, then water quench, followed by tempering at 600℃ for 3 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0044] like Figure 2 photographs of the cladding transition zone and Figure 3 The matrix structure is shown in the photograph. The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the cladding layer at the tooth tip reaches 1520HV, the hardness of the matrix is ​​380HV, and the interfacial bonding strength is ≥500MPa.

[0045] Example 2

[0046] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0047] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 50μm. The substrate is then preheated to 200℃ in an induction heating furnace and held for 15 minutes. A laser power of 3.5kW, a spot diameter of 1.5mm, and a cladding scanning speed of 6mm / s are set. Molybdenum boride-reinforced iron-based alloy powder is clad layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 18wt% Mo2B, 5wt% vanadium carbide (10μm particle size), 3wt% titanium nitride composite ceramic (20μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a surface microtexture.

[0048] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 0.3 mm, a groove width of 0.5 mm, a groove spacing of 2 mm, and a surface roughness Ra = 50 μm. Subsequently, a furan resin sand mold containing 2% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.2 mm gap. Before casting, the preform is gradually heated to 300°C at a rate of 10°C / s using induction heating and held for 5 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 200°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres and resin sand are uniformly mixed.

[0049] S3: Melt the cast steel at 1600℃ and rapidly pour it at a casting temperature of 1520℃. Before pouring, apply flux with a rare earth oxide content of 1.0% to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxide is Y2O3 or CeO2, which releases active rare earth elements during decomposition. S4: After the casting cools naturally to 550℃, open the mold and use a vibrating sand removal machine to clean residual sand particles. Then, cut off the riser and gating the flash to a surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0050] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 850℃ for 1.5 hours, then water quench, followed by tempering at 500℃ for 2.0 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0051] The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the cladding layer at the tooth tip reaches 1400HV, the hardness of the matrix is ​​300HV, and the interfacial bonding strength is ≥500MPa.

[0052] Example 3

[0053] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0054] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 25μm. The substrate is then preheated to 250℃ in an induction heating furnace and held for 10 minutes. A laser power of 4.75kW, a spot diameter of 2.25mm, and a cladding scanning speed of 9mm / s are set. Molybdenum boride-reinforced iron-based alloy powder is clad layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 15wt% Mo2B, 10wt% vanadium carbide (30μm particle size), 5.50wt% titanium nitride composite ceramic (50μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a micro-textured surface.

[0055] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 0.75 mm, a groove width of 1.0 mm, a groove spacing of 3.5 mm, and a surface roughness Ra = 25 μm. Subsequently, a furan resin sand mold containing 6% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.5 mm gap. Before casting, the preform is gradually heated to 375°C at a rate of 12.5°C / s using induction heating and held for 10 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 250°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0056] S3: Melt the cast steel at 1625℃ and rapidly pour it at a casting temperature of 1540℃. Before pouring, apply flux with a rare earth oxide content of 3.0% to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxide is Y2O3 or CeO2, which releases active rare earth elements during decomposition. S4: After the casting cools naturally to 550℃, open the mold and use a vibrating sand removal machine to clean residual sand particles. Then, cut off the riser and gating the flash to a surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0057] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 875℃ for 1.5 hours, then water quench, followed by tempering at 550℃ for 3.0 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0058] The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the tooth tip cladding layer reaches 1600HV, the hardness of the matrix is ​​350HV, and the interface bonding strength is ≥500MPa.

[0059] Example 4

[0060] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0061] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 10 μm. The substrate is then preheated to 300°C in an induction heating furnace and held for 8 minutes. A laser power of 6.0 kW, a spot diameter of 3.0 mm, and a cladding scanning speed of 12 mm / s are set. Molybdenum boride-reinforced iron-based alloy powder is clad layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 13 wt% Mo2B, 15 wt% vanadium carbide (50 μm particle size), 8 wt% titanium nitride composite ceramic (80 μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5 mm and a surface microtexture.

[0062] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 1.2 mm, a groove width of 1.5 mm, a groove spacing of 5 mm, and a surface roughness Ra = 10 μm. Subsequently, a furan resin sand mold containing 10% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.8 mm gap. Before casting, the preform is gradually heated to 450°C at a rate of 15°C / s using induction heating and held for 15 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 300°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0063] S3: Melt the cast steel at 1650℃ and rapidly pour it at a casting temperature of 1560℃. Before pouring, apply flux with a rare earth oxide content of 5.0% to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxide is Y2O3 or CeO2, which releases active rare earth elements during decomposition. S4: After the casting cools naturally to 550℃, open the mold and use a vibrating sand removal machine to clean residual sand particles. Then, cut off the riser and gating the flash to a surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0064] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 900℃ for 1.5 hours and then water quench, followed by tempering at 600℃ for 4.0 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0065] The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the tooth tip cladding layer reaches 1800HV, the hardness of the matrix is ​​400HV, and the interface bonding strength is ≥500MPa.

[0066] Example 5

[0067] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0068] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 38μm. The substrate is then preheated to 215℃ in an induction heating furnace and held for 7 minutes. A laser power of 4.2kW, a spot diameter of 2.1mm, and a cladding scanning speed of 8mm / s are used to clad molybdenum boride-reinforced iron-based alloy powder layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 18wt% Mo2B, 7wt% vanadium carbide (particle size 25μm), 4wt% titanium nitride composite ceramic (particle size 35μm), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a surface microtexture.

[0069] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 0.5 mm, a groove width of 0.7 mm, a groove spacing of 3 mm, and a surface roughness Ra = 38 μm. Subsequently, a furan resin sand mold containing 4% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.3 mm gap. Before casting, the preform is gradually heated to 320°C at a rate of 12°C / s using induction heating and held for 8 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 220°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0070] S3: The cast steel is melted at 1620℃ and rapidly cast at a pouring temperature of 1535℃. Before casting, a flux containing 2.0% rare earth oxides is applied to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxides are Y₂O₃ or CeO₂, which release active rare earth elements during decomposition.

[0071] S4: After the casting has cooled naturally to 550℃, it is opened from the mold. The residual sand particles are cleaned by a vibrating sand removal machine. Then the gating gate is cut off and the flash is ground until the surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0072] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 870℃ for 1.5 hours, then water quench, followed by tempering at 520℃ for 2.5 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0073] The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the tooth tip cladding layer reaches 1480HV, the hardness of the matrix is ​​320HV, and the interfacial bonding strength is ≥500MPa.

[0074] Example 6

[0075] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0076] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 12μm. The substrate is then preheated to 290℃ in an induction heating furnace and held for 15 minutes. A laser power of 5.8kW, a spot diameter of 1.6mm, and a cladding scanning speed of 11mm / s are set. Molybdenum boride-reinforced iron-based alloy powder is clad layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 12wt% Mo2B, 13wt% vanadium carbide (45μm particle size), 7wt% titanium nitride composite ceramic (70μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a surface microtexture.

[0077] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 1.0 mm, a groove width of 1.3 mm, a groove spacing of 4 mm, and a surface roughness Ra = 12 μm. Subsequently, a furan resin sand mold containing 9% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.7 mm gap. Before casting, the preform is gradually heated to 430°C at a rate of 14°C / s using induction heating and held for 14 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 295°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0078] S3: Cast steel is melted at 1645℃ and rapidly cast at a pouring temperature of 1555℃. Before casting, a flux containing 4.0% rare earth oxides is applied to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxides are Y2O3 or CeO2, which release active rare earth elements during decomposition.

[0079] S4: After the casting has cooled naturally to 550℃, it is opened from the mold. The residual sand particles are cleaned by a vibrating sand removal machine. Then the gating gate is cut off and the flash is ground until the surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0080] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 890℃ for 1.5 hours, then water quench, followed by tempering at 580℃ for 3.8 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0081] The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the tooth tip cladding layer reaches 1720HV, the hardness of the matrix is ​​390HV, and the interfacial bonding strength is ≥500MPa.

[0082] Example 7

[0083] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0084] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 45μm. The substrate is then preheated to 265℃ in an induction heating furnace and held for 15 minutes. A laser power of 3.7kW, a spot diameter of 2.8mm, and a cladding scanning speed of 7mm / s are set. Molybdenum boride-reinforced iron-based alloy powder is clad layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 20wt% Mo2B, 5wt% vanadium carbide (15μm particle size), 3wt% titanium nitride composite ceramic (25μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a micro-textured surface.

[0085] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 0.4 mm, a groove width of 0.5 mm, a groove spacing of 2 mm, and a surface roughness Ra = 45 μm. Subsequently, a furan resin sand mold containing 3% alumina hollow spheres (1.0 mm particle size) is prepared, and the preform is embedded into the mold cavity, leaving a 0.2 mm gap. Before casting, the preform is gradually heated to 380°C at a rate of 10°C / s using induction heating and held for 6 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 255°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0086] S3: The cast steel is melted at 1605℃ and rapidly cast at a pouring temperature of 1520℃. Before casting, a flux containing 1.0% rare earth oxides is applied to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxides are Y₂O₃ or CeO₂, which release active rare earth elements during decomposition.

[0087] S4: After the casting has cooled naturally to 550℃, it is opened from the mold. The residual sand particles are cleaned by a vibrating sand removal machine. Then the gating gate is cut off and the flash is ground until the surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0088] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 860℃ for 1.5 hours and then water quench, followed by tempering at 540℃ for 2.2 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0089] The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the tooth tip cladding layer reaches 1550HV, the hardness of the matrix is ​​305HV, and the interfacial bonding strength is ≥500MPa.

[0090] Example 8

[0091] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0092] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 50μm. The substrate is then placed in an induction heating furnace and preheated to 235℃ for 15 minutes. A laser power of 6.0kW, a spot diameter of 3.0mm, and a cladding scanning speed of 9mm / s are set. Molybdenum boride-reinforced iron-based alloy powder is clad layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 16wt% Mo2B, 15wt% vanadium carbide (50μm particle size), 8wt% titanium nitride composite ceramic (80μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a surface microtexture.

[0093] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 1.2 mm, a groove width of 1.5 mm, a groove spacing of 5 mm, and a surface roughness Ra = 50 μm. Subsequently, a furan resin sand mold containing 10% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.8 mm gap. Before casting, the preform is gradually heated to 450°C at a rate of 15°C / s using induction heating and held for 15 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 300°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0094] S3: Melt the cast steel at 1650℃ and rapidly pour it at a casting temperature of 1560℃. Before pouring, apply flux with a rare earth oxide content of 5.0% to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxide is Y2O3 or CeO2, which releases active rare earth elements during decomposition. S4: After the casting cools naturally to 550℃, open the mold and use a vibrating sand removal machine to clean residual sand particles. Then, cut off the riser and gating the flash to a surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0095] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 900℃ for 1.5 hours and then water quench, followed by tempering at 600℃ for 4.0 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0096] The wear-resistant bucket teeth obtained through the aforementioned molding process have the following properties: the hardness of the tooth tip cladding layer reaches 1800HV, the hardness of the matrix is ​​400HV, and the interface bonding strength is ≥500MPa.

[0097] Example 9

[0098] A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets includes the following steps:

[0099] S1: The low-alloy steel substrate is sandblasted with brown corundum to achieve a surface roughness Ra of 22μm. The substrate is then preheated to 305℃ in an induction heating furnace and held for 15 minutes. A laser power of 4.9kW, a spot diameter of 1.9mm, and a cladding scanning speed of 12mm / s are set. Molybdenum boride-reinforced iron-based alloy powder is clad layer by layer onto the substrate surface. The molybdenum boride-reinforced iron-based alloy powder consists of 16wt% Mo2B, 9wt% vanadium carbide (35μm particle size), 5wt% titanium nitride composite ceramic (50μm particle size), and the remainder is iron powder. These four components form a composite powder, ultimately forming a wear-resistant preform with a total thickness of 5mm and a surface microtexture.

[0100] S2: A dovetail groove array is machined on the back of the cladding preform, with a groove depth of 0.8 mm, a groove width of 1.0 mm, a groove spacing of 3.5 mm, and a surface roughness Ra = 22 μm. Subsequently, a furan resin sand mold containing 6% alumina hollow spheres (1.0 mm in diameter) is prepared, and the preform is embedded into the mold cavity, leaving a 0.6 mm gap. Before casting, the preform is gradually heated to 340°C at a rate of 11°C / s using induction heating and held for 10 minutes, then heated to 400°C. Simultaneously, the sand mold is preheated to 240°C using infrared radiation heating to ensure interface thermal stress matching. Preferably, the alumina hollow spheres are uniformly mixed with the resin sand.

[0101] S3: The cast steel is melted at 1610℃ and rapidly cast at a pouring temperature of 1540℃. Before casting, a flux containing 3.0% rare earth oxides is applied to the back of the preform, with a coating thickness of 0.2mm. The high temperature of the molten steel allows the flux to penetrate into the dovetail groove and the reserved gap, forming a metallurgical bonding transition layer. Preferably, the rare earth oxides are Y₂O₃ or CeO₂, which release active rare earth elements during decomposition.

[0102] S4: After the casting has cooled naturally to 550℃, it is opened from the mold. The residual sand particles are cleaned by a vibrating sand removal machine. Then the gating gate is cut off and the flash is ground until the surface roughness Ra≤12.5μm, completing the initial machining of the casting.

[0103] S5: Place the casting in a box furnace for quenching and tempering: first, hold at 850℃ for 1.5 hours, then water quench, followed by tempering at 510℃ for 3.0 hours and air cooling to optimize the matrix structure and residual stress distribution.

[0104] The wear-resistant bucket teeth obtained through the aforementioned forming process have the following properties: the hardness of the cladding layer at the tooth tip reaches 1650 HV, the hardness of the substrate is 350 HV, and the interfacial bonding strength is ≥500 MPa. In Examples 1 to 9, the tooth tip region is a laser cladding layer, and the substrate is low-carbon alloy steel.

[0105] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A laser cladding-composite casting integrated molding process for wear-resistant bucket teeth of ultra-large excavator buckets, characterized in that, Includes the following steps: S1: Substrate pretreatment and laser cladding: Low alloy steel substrate is selected, and after surface sandblasting and rust removal, it is preheated. Then, using laser cladding equipment, molybdenum boride reinforced iron-based alloy powder is clad layer by layer on the pre-embedded metal substrate to form a wear-resistant preform. S2: Composite sand mold preparation and pre-embedding: Place the clad wear-resistant preform into the resin sand mold, and preheat the preform and sand box before casting; S3: Alloy melting and casting: Melt cast steel, control the temperature of molten steel, quickly pour into the mold, use the high temperature of molten steel to partially remelt the back of the substrate, and apply flux to the back of the substrate before casting. S4: Directional cooling and sand removal: After the casting has cooled naturally, the mold is opened, the residual sand particles are removed by vibration, the gating and riser are cut off and the flash is ground off. S5: Tempering and heat treatment strengthening: Quenching and tempering treatment of castings.

2. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 1, characterized in that, Includes the following steps: S1: Substrate pretreatment and laser cladding: Low alloy steel substrate is selected. After surface sandblasting and rust removal, it is preheated to 200-300℃. Using laser cladding equipment, molybdenum boride reinforced iron-based alloy powder is clad layer by layer on the pre-embedded metal substrate. The laser power is 3.5-6.0kW, the spot diameter is 1.5-3.0mm, and the scanning speed is 6-12mm / s, forming a wear-resistant preform with surface microtexture. S2: Composite sand mold preparation and pre-embedding: The cladding preform is placed as an embedded block into the resin sand mold. Before casting, the preform and the sand box are preheated using a gradient preheating process. S3: Alloy melting and casting: Melt cast steel, control the melting temperature to 1600-1650℃, and quickly cast at a casting temperature of 1520-1560℃. Use the high temperature of the molten steel to partially remelt the back of the substrate. Apply flux to the back of the substrate before casting. S4: Directional cooling and sand removal: After the casting has cooled naturally to below 600℃, the mold is opened, the residual sand particles are removed by vibration, the gating and riser are cut off and the flash is ground off. S5: Tempering and heat treatment strengthening: After holding at 850-900℃, oil cooling / water quenching, followed by tempering at 500-600℃ for 2.0-4.0 hours and air cooling.

3. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 1, characterized in that: The back of the pre-embedded metal substrate is an array of dovetail grooves with a depth of 0.3-1.2mm, a groove spacing of 2-5mm, a groove width of 0.5-1.5mm, and a surface roughness Ra≤50μm.

4. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 2 or 3, characterized in that: The gradient preheating process includes preheating the cladding layer to 300-450℃ and preheating the resin sand casting mold to 200-300℃. The heating method is a combination of induction heating and infrared radiation heating.

5. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 4, characterized in that: The gradient preheating adopts a staged temperature control strategy. The cladding layer is first heated to 300℃ at a rate of 10-15℃ / s, held for 5-15 minutes, and then heated to the target temperature. The casting sand mold is heated by infrared radiation in zones.

6. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 1, characterized in that, The molybdenum boride-reinforced iron-based alloy powder has an alloy composition of 8-20 wt% Mo2B, 5.0-15 wt% vanadium carbide, 3.0-8.0 wt% titanium nitride composite ceramic particles and iron powder, wherein the vanadium carbide particle size is 10-50 μm and the titanium nitride particle size is 20-80 μm.

7. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 1, characterized in that: The resin sand casting mold is locally supplemented with 2-10% alumina hollow spheres as a heat buffer medium. The alumina hollow spheres are uniformly mixed with the resin sand and oriented in the area where the wear-resistant preform is placed. Their low thermal conductivity slows down the solidification rate of the interface area and matches the thermal expansion difference between the cladding layer and the substrate.

8. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 1, characterized in that: The flux contains 1-5% rare earth oxides, namely Y2O3 or CeO2, and the rare earth elements release active rare earth elements during the decomposition process.

9. The integrated forming process of laser cladding-composite casting for wear-resistant bucket teeth of ultra-large excavator buckets according to claim 1, characterized in that: The wear-resistant preform has a dovetail groove array on the back to accommodate the infiltration of cast metal to form a metallurgical bonding transition layer.

10. Wear-resistant bucket teeth prepared according to any one of the integrated molding processes described in claims 1-9, characterized in that: The tip area of ​​the bucket teeth is covered by a laser cladding layer with a hardness of HV1400-1800; the substrate is low-carbon alloy steel with a hardness of HV300-400 and an interface bonding strength ≥500MPa.

Citation Information

Patent Citations

  • Preparation method of particle reinforced iron base super wear-resisting bucket tooth

    CN108160923A